PITUTUR LUHUR DALAM TEMBANG GAMBUH SERAT WULANGREH - Rika Ayu Putrimarini; Sumarwati Sumarwati; Dewi Pangestu Said (Universitas Sebelas Maret, 2025)
Javanese noble advice (pitutur luhur Jawa) is noble teachings handed down by the ancestors. But now, with the advancement of technology, it is difficult for people to understand and apply that Javanese noble advice. The purpose of this study is to describe the sublime Javanese noble advice in the song Gambuh Serat Wulangreh. This research is qualitative descriptive research with a content analysis approach. The data used in this study are the Javanese noble advice of the Tembang Gambuh Serat Wulangreh, which was obtained from the data source in the form of a document, namely the text of the Tembang Gambuh Serat Wulangreh. Based on the results of data analysis, it was concluded that the Javanese noble advice in the Gambuh Serat Wulangreh song includes 5 dimensions, namely: (1) the dimensions of ethics and manners are shown by avoiding arrogant attitudes towards others; (2) the dimensions of justice and truth are shown by not looking at people with one eye; (3) the dimensions of social relations are shown by the way they behave in the social environment; (4) the dimension of intimacy is shown by maintaining the trust given by others; and (5) the tolerance dimension is shown by appreciating the gifts of others. This research can provide an easier understanding of the noble advice in a Tembang, so that can be used as learning material in schools.